2009
DOI: 10.1111/j.1398-9995.2009.02110.x
|View full text |Cite
|
Sign up to set email alerts
|

Human milk fortifier in preterm babies: source of cow’s milk protein sensitization?

Abstract: Supplements added to human milk might expose infants to allergens such as cow’s milk protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…However NEC is the most important differential diagnosis to exclude in preterm neonates with rectal bleeding especially if accompanied with signs of systemic instability. As seen in the literature review 3 preterm cases and 1 term newborn had presented with signs of NEC and initially treated as such who later were diagnosed to have allergic proctocolitis 1,3,7 . Two of them even received NEC treatment twice 1,3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However NEC is the most important differential diagnosis to exclude in preterm neonates with rectal bleeding especially if accompanied with signs of systemic instability. As seen in the literature review 3 preterm cases and 1 term newborn had presented with signs of NEC and initially treated as such who later were diagnosed to have allergic proctocolitis 1,3,7 . Two of them even received NEC treatment twice 1,3 .…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of CMPA in the first year of life is 2-7% and is reported as 0.34-2 % in preterms 2 , although there seems to be an increase in recent years in preterm population. Since 1990, 20 cases who were diagnosed to have CMPA during neonatal period have been reported in English literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14] . The most common clinical sign of CMPA is bloody stool in a well-appearing infant.…”
mentioning
confidence: 99%
“…The incidence of bloody stools with no other gastrointestinal symptoms was of interest, but not significant. This finding could be the result of a cow's milk protein sensitization from the powdered Human milk fortification 31 and it may prove beneficial to follow in future studies with larger samples. Increased protein administration, by way of early fortification, to preterm infants at an early age brings into question whether or not they can tolerate the renal solute load, but evidence clearly shows that even in extremely preterm human milk (<28 weeks) the protein content averages 2.3 g dl À132 and the addition of human milk fortifier adds only 0.28 g per 25 ml, which is still a minimal amount of protein when compared with the recommended daily intake as mentioned previously.…”
Section: Discussionmentioning
confidence: 99%
“…In the premature infants, immature intestinal tissue and the problems of the intestinal epithelium (nutritional restriction, ischemic damage, free radicals) increase the intestinal permeability [6]. Therefore, these infants become more sensitive to food allergy [6].…”
Section: Discussionmentioning
confidence: 99%
“…The incidences of skin signs such as atopic dermatitis, gastrointestinal symptoms such as blood in the stool, diarrhea and vomiting and respiratory symptoms such as wheezing without the presence of an infection are 50-60%, 50-60% and 20-30%, respectively [5]. Premature infants are exposed to cow milk proteins at earlier periods of the life by consuming formulae and breast milk fortifiers derived from cow milk or via the milk consumed by the mother [6]. In the newborns that develop allergy, it is reported that there is a cell-mediated reaction and that increased number of T-helper-2 cells and decreased number of regulatory T lymphocytes trigger the food sensitivity [2].…”
Section: Introductionmentioning
confidence: 99%